SINCERITY: A VALUE REALITY IN BUILDING RELIGIOSITY FOR ACCOUNTING STUDENTS - Rahmawati Hanny Yustrianthe (Erudio Journal of Educational Innovation, 2019)
This research aims to describe the value reality in building religiosity for accounting students. This research uses spiritual paradigm with qualitative approach and ulul albab perspective in constructing ontological, epistemological, and research method. The data was obtained through observation, interviews, and library research in one of the reputable Islamic-based universities in Indonesia which has an accounting program. Using the methods of prayer, dhikr, tafakkur, and tawakkal, this research has succeeded in describing the value as a reflection of faith. Therefore, it is expected that accounting education is able to produce students with religious, amanah, and noble character.